Observation of insulating–insulating monoclinic structural transition in macro‐sized VO2 single crystals [Phys. Status Solidi RRL 5, No. 3, R107–R109 (2011)]. Issue 3 (23rd February 2015) - Mun, Bongjin Simon; Chen, Kai; Leem, Youngchul; Dejoie, Catherine; Tamura, Nobumichi; Kunz, Martin; Liu, Zhi; Grass, Michael E.; Park, Changwoo; Yoon, Joonseok; Lee, Y. Yvette; Ju, Honglyoul
Abstract : In our article, we reported the observation of monoclinic M2 to M1 structural phase transition in VO2 single crystal near the temperature of ∼49 °C. However, the re‐examination of Laue patterns reveals that previously defined monoclinic M1 and M2 phases can be interpreted as monoclinic M2 and triclinic T phases instead. Careful experimental geometry calibration and further refinement of the lattice parameter ratios and angles show that monoclinic M2 and triclinic T phases fit better with the experimental data. On the other hand, our previous misidentification of the insulating phases does NOT affect the conclusions of our article. (© 2015 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim)